2021
DOI: 10.2478/adms-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Regularities of Adsorption of Α-Oxypropionic Acid By Natural Zeolite

Abstract: Wastewaters from dairy processing factories contaminated with α-oxypropionic acid were monitored. Theoretical analysis of industrial wastewater treatment methods on zeolites of Sokyrnytsia deposit was carried out. The process of sorption of α-oxypropionic (α-oxypropionic) acid by natural zeolite of Sokyrnytsia deposit was considered. It was established that the most economically advantageous and safe is the method of adsorption using a natural sorbent - zeolite, which provides the lowest concentration of conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
1
Order By: Relevance
“…Perbandingan Si/Al pada zeolite menentukan kerapatan muatan dalam struktur kristalnya, sehingga mempengaruhi tingkat adsorpsi dari adsorben tersebut (Atikah, 2017). Zeolite alam dapat dimanfaatkan untuk mengadsorpsi asamasam organik seperti asam asetat, asam humat, dan asam α-oksipropionat (Wang, Terdkiatburana dan Tadé, 2008;Narin, 2017;Kareem dan Dawagreh, 2018;Sabadash et al, 2021)zeolites are found in the following locations: zeolitic tuffs are located at Jabal Aritayn (JNZ-4. Mekanisme adsorpsi asam organik dikontrol oleh reaksi kimia yang dimungkinkan melibatkan reaksi sederhana antara anion asam dengan oksida dan kation divalen pada zeolite (Wang, Terdkiatburana dan Tadé, 2008;Narin, 2017) Tabel 5 menunjukkan kelompok senyawa dominan pada semua perlakuan asap cair adalah asam organik, alkohol, karbonil, furan, dan fenol, berdasarkan dari persentase area terbesar, menunjukkan bahwa komponen utama dari asap cair adalah asam organik.…”
Section: Identifikasi Komponen Senyawa Asap Cairunclassified
“…Perbandingan Si/Al pada zeolite menentukan kerapatan muatan dalam struktur kristalnya, sehingga mempengaruhi tingkat adsorpsi dari adsorben tersebut (Atikah, 2017). Zeolite alam dapat dimanfaatkan untuk mengadsorpsi asamasam organik seperti asam asetat, asam humat, dan asam α-oksipropionat (Wang, Terdkiatburana dan Tadé, 2008;Narin, 2017;Kareem dan Dawagreh, 2018;Sabadash et al, 2021)zeolites are found in the following locations: zeolitic tuffs are located at Jabal Aritayn (JNZ-4. Mekanisme adsorpsi asam organik dikontrol oleh reaksi kimia yang dimungkinkan melibatkan reaksi sederhana antara anion asam dengan oksida dan kation divalen pada zeolite (Wang, Terdkiatburana dan Tadé, 2008;Narin, 2017) Tabel 5 menunjukkan kelompok senyawa dominan pada semua perlakuan asap cair adalah asam organik, alkohol, karbonil, furan, dan fenol, berdasarkan dari persentase area terbesar, menunjukkan bahwa komponen utama dari asap cair adalah asam organik.…”
Section: Identifikasi Komponen Senyawa Asap Cairunclassified